A fast H.264 intra prediction algorithm using macroblock properties - YANG, Chun-Ling; PO, Lai-Man; LAM, Wing-Hong (2004 International Conference on Image Processing, 2004. ICIP '04, 2004)
In the newest video coding standard of H.264, intra frame prediction is conducted in the spatial domain. There are two types of intra prediction for luma - Intra/spl I.bar/16/spl times/16 does prediction for the whole 16/spl times/16 luma macroblock and Intra/spl I.bar/4/spl times/4 does prediction for 4/spl times/4 block. Four and nine modes are supported by Intra/spl I.bar/16/spl times/16 and Intra/spl I.bar/4/spl times/4, respectively. The full search algorithm is used in the JVT reference software to choose the best modes, however it is very computationally expensive. In this paper, a new fast intra prediction algorithm using macroblock properties (FIPAMP) is proposed. Experimental results show that the proposed fast algorithm can achieve 10% to 40% computation reduction while maintaining similar PSNR and bit rate performance of H.264 codes.